2007
DOI: 10.1007/s12038-007-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

A mechanical model of wing and theoretical estimate of taper factor for three gliding birds

Abstract: We tested a mechanical model of wing,which was constructed using the measurements of wingspan and wing area taken from three species of gliding birds.In this model,we estimated the taper factors of the wings for jackdaw (Corrus monedula), Harris' hawk (Parabuteo unicinctas) and Lagger falcon (Falco jugger) as 1.8, 1.5 and 1.8,respectively. Likewise, by using the data linear regression and curve estimation method,as well as estimating the taper factors and the angle between the humerus and the body, we calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nonetheless, once our knowledge about applying accelerometers improves, the high‐resolution time and energy data they will likely provide will be valuable for comparative studies between bird species (Prinzinger et al 2002, Zahedi and Khan 2007). Furthermore, such data may be useful for conservation physiologists (Wikelski and Cooke 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, once our knowledge about applying accelerometers improves, the high‐resolution time and energy data they will likely provide will be valuable for comparative studies between bird species (Prinzinger et al 2002, Zahedi and Khan 2007). Furthermore, such data may be useful for conservation physiologists (Wikelski and Cooke 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The soaring flight is a type of gliding in which both wings stop flapping and are stretched out; however, the lifting force can derive from ascending thermal air, and the thrust derives from gliding to another ascending thermal air or from orographic uplift air. In both gliding and soaring, the energetic cost is very low (Heers et al, 2016; Henningsson & Hedenström, 2011; Pennycuick, 2002; Richardson et al, 2018; Thielicke & Stamhuis, 2018; Zahedi & Khan, 2007). For birds, the main obstacles during flight are the torsional and bending loads, which impact the feathers and transmit these biomechanical loads to the wing bones in different manners depending on the flight style.…”
Section: Introductionmentioning
confidence: 99%
“…By observing the wing shape change in raptorsized birds, such as steppe eagle, swift, gull, albatross, etc., biologists have found that the arm wing (inboard section containing the secondary feathers) moves forward with the wrist joint, while the hand wing (outer section of the wing, consisting of the primary feathers) sweeps to the rear. The dihedral angles of the hand and arm wings also show an opposite change pattern [16][17][18][19][20][21][22][23]. The multi-section morphing wing can realize the centroid self-trim compensation during the morphing process by the antisymmetric coordinated deformation of the inner and outer wing sections.…”
Section: Introductionmentioning
confidence: 99%